Toll-like receptor 4 and cytotoxic T cells CD8+ are prognostic markers in type 1 Diabetes Mellitus - Noor AlHuda Ghanem Hadi Al-Fatlawi (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the correlation between toll-like receptor 4 and cytotoxic T cells in patients with type-1 diabetes mellitus. Method: The cross-sectional, case control study was conducted at Al-Manatharah Hospital in the Al-Najaf province of Iraq from June 2021 to December 2021, and comprised patients of either gender aged 20-69 years having type-1 diabetes mellitus in group A, and healthy subjects in control group B. From all the subjects, 4ml blood was collected by vein puncture. Fasting blood glucose and lipid profile were estimated using a precipitant kit. Also measured were toll-like receptor 4 and cytotoxic T cell levels using an enzyme-linked immunosorbent assay kit. Data was also noted on age, gender and body mass index. Data was analysed using SPSS version 23 Results: Of the 100 subjects, 60(60%) were cases; 30(50%) males and as many females with mean age 59.21±18.092 years. The remaining 40(40%) were controls; 20(50%) males and as many females with mean age 42.076±11.019 years. BMI values were not significantly different between the groups (p>0.05), and all lipid profile values were significantly higher in group A compared to group B (p<0.05) except high-density lipoprotein which was higher in group B compared to group A (p<0.05). Group A patients had significantly higher levels of toll-like receptor 4 and cytotoxic T cell than group B subjects (p<0.05). Conclusion: A significant relationship was found between type-1 diabetes and higher levels of toll-like receptor 4 and cytotoxic T cells. Keywords: Diabetes mellitus, Toll-like receptor 4, Cytotoxic T cells, CD8.